Direct and Indirect Effects of Neuroticism on Internet Addiction in College Students: A Structure Equation Modeling Analysis. - Zhang, Yang (Psychological Reports, 2021)
In the recent decade, increased severity of Internet addiction has been the focus of considerable attention. This research aimed to explore the relationships between neuroticism and Internet addiction. A total of 459 undergraduate students in China participating in this study completed self-report measures of neuroticism, impulsivity, and Internet addiction. The results showed that neuroticism, impulsivity, and Internet addiction were significantly and positively correlated with one other. The structural equation modeling approach indicated that impulsivity, in part, mediated the effect of neuroticism on Internet addiction. An important indirect path from neuroticism to Internet addiction through impulsivity was exposed using the bootstrap method. The outcomes of previous studies were expounded on to define how neuroticism affects Internet addiction.